Internet in the service of parents of children with intellectual disability (Virtualizing the lives of people with disabilities, 2021)
Despite the changes that have taken place in recent years, there are plenty of activities that are still inaccessible to categories of excluded and marginalized people due to numerous barriers in the social space. New media, and among them the Internet, offer a real chance to get rid of these limitations at least partially. Therefore, in this paper, I try to present the importance and functions of the Internet as attributed by parents of people with disabilities. The research conducted was qualitative in nature, and data analysis was based on the procedures of the grounded theory methodology.